2023
DOI: 10.1111/tid.14012
|View full text |Cite
|
Sign up to set email alerts
|

BK virus genotypes and humoral response in kidney transplant recipients with BKV associated nephropathy

Abstract: Background Among kidney transplant recipients (KTR) with BK virus associated nephropathy (BKVN), BKV genotypes’ evolution and anti‐BKV humoral response are not well established. We aim to analyze BKV replication and genetic evolution following transplantation, and characterize concomitant anti‐BKV‐VP1 humoral response. Methods We retrospectively analyzed 32 cases of biopsy‐proven BKVN. Stored plasma and kidney biopsies were tested for BKV viral load, and VP1 sequencing performed on positive samples. BKV–VP1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This finding, absent in other countries, suggests a unique evolutionary pattern and a mutation specific to a particular geographic region. Furthermore, Gras et al revealed that BKV subtypes derived from baseline donor kidney biopsies often differ from those obtained from biopsy samples during BKVAN diagnosis [46]. This observation of a genotype switch suggests genetic heterogeneity within clinically prevalent BKV strains, underscoring the necessity of the accurate monitoring of the viral load across varying subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding, absent in other countries, suggests a unique evolutionary pattern and a mutation specific to a particular geographic region. Furthermore, Gras et al revealed that BKV subtypes derived from baseline donor kidney biopsies often differ from those obtained from biopsy samples during BKVAN diagnosis [46]. This observation of a genotype switch suggests genetic heterogeneity within clinically prevalent BKV strains, underscoring the necessity of the accurate monitoring of the viral load across varying subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The virological and immunological determinants of the progression from self-limited BKPyV viruria or viremia to BKPyV nephropathy in kidney transplant recipients are poorly understood. As for the source of BKPyV, the donor origin has been repeatedly suggested, although virus reactivation in recipients can also occur, and both sources may not be mutually exclusive [12][13][14][15].…”
Section: Kidney Graft Involvementmentioning
confidence: 99%
“…Virological and immunological determinants of the progression from self-limited BKPyV viruria or viremia to BKPyV nephropathy in kidney transplant recipients are poorly understood and the source of BKPyV could be either the urinary tract of the donor or the recipient, although both sources may not be mutually exclusive [12][13][14].…”
Section: Kidney Graft Involvementmentioning
confidence: 99%